Perbandingan Kinerja Protokol ZRP (Zone Routing Protocol) dan HWMP (Hybrid Wireless Mesh Protocol) pada MANET (Mobile Ad hoc Network) - Miftaqul Novandi; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
MANET is a dynamic wireless network, because each node can move freely so the topology network often changes unpredictably. Conditions in the changing topology due to an effect on the performance of the routing protocol used on MANET. A mobile device in MANET that is implemented as a mobile node can be a tablet, laptop and smartphone. MANET's routing protocols have several types, namely reactive, proactive and hybrid (a combination of reactive and proactive routing protocols). Previous research on the performance of the ZRP and HWMP protocols which is hybrid routing protocols, using the scope of the WMN (Wireless Mesh Network). WMN has a range of a devices that‘s not wide and topology that is used in a static state. This research using the scope of MANET, focusing on user devices, mobility built without infrastructure, and ad-hoc capabilities. The topology in a network that moves dynamically and the implementation in a broad scope is able to influence the performance of the ZRP and HWMP protocols as the routing protocol that we want to simulate in this study. With this routing protocol changes will be observed that occur based on testing parameters such as throughput, packet delivery ratio (PDR), normalized routing load, end-to-end delay and convergence time. The scenario test is done using static and dynamic nodes, and Network Simulator 2 (NS-2) as a test simulation. The simulation results that have been obtained are concluded that ZRP routing protocol is more dominant for the five test parameters carried out in the dynamic topology scope, while for the static topology is more dominated by HWMP.